Avaliação da atividade vasorrelaxante da alga marinha brasileira Dictyota pulchella Hörning & Schnetter em ratos normotensos - Queiroz, Thyago Moreira de (2011)
The pharmacological effects induced by CH2Cl2/MeOH extract (EDP) and Hexane/EtOAc phase (FDP) from the Brazilian alga Dictyota pulchella were studied on the cardiovascular system of Wistar rats using a combined in vivo and in vitro approach. All protocols in this study were approved by the CEPA/LTF (protocol nº 0208/10). In normotensive conscious male rats, EDP injections (5; 10; 20 and 40 mg/kg, i.v., randomly) produced hypotension (-4.1 ± 1.34; -7.0 ± 2.4; -46.9 ± 1.3 and - 54.8 ± 4.3%; respectively) and bradycardia (-2.1 ± 1.6; -4.0 ± 2.3; -66.8 ± 5.2 and - 74.7 ± 4.5%; respectively) (n=5). Isolated superior mesenteric artery rings (1-2 mm) were suspended by cotton threads for isometric tension recordings in a Tyrode s solution at 37 ºC, gassed with a 95% O2 and 5% CO2, under a resting tension of 0.75g. In phenylephrine (Phe, 1μM)-pre-contracted rings, EDP (0.01 500 μg/mL) induced a concentration-dependent relaxation (Maximum Response = 101.4 ± 4.5%; EC50 = 22.35 ± 5.09 μg/mL) and this effect was not modified by removal of the vascular endothelium (MR = 103.3 ± 8.3%; EC50 = 21.43 ± 8.98 μg/mL, n=7). Similar results were found in the presence of FDP (0.01 500 μg/mL). FDP induced a concentration-dependent vasodilatation in both endothelium-intact (MR = 80.6 ± 5.8%; EC50 = 24.1 ± 8.95 μg/mL, n=6) or endothelium-denuded mesenteric artery rings (MR = 95.6 ± 7.5%; EC50 = 23.7 ± 5.65 μg/mL, n=6). Based on the preliminary results, the subsequent experiments were performed in rings without endothelium. To appreciate the involvement of potassium channels, the preparations were preincubated with Tyrode s modified solution, KCl (20 mM) or with non-selective K+ channel blocker, tetraethylammonium (TEA, 3 mM). In both preparations the vasorelaxant activity was not changed. In the presence of a tromboxane A2 agonist U-46619 (100 nM), EDP induced concentration-dependent vasodilatation (MR = 90.3 ± 7.8%; EC50 = 24.63 ± 4.04 μg/mL, n=6) was similar to the response found under Phe-induced. After exposure to high concentrations of extracellular K+ (KCl, 60 mM), the EDP induced concentration-dependent vasodilatation (MR = 97.7 ± 4.0%; EC50 = 34.57 ± 5.11 mg/mL; n=6). In the same experimental condition, FDP induced concentration-dependent vasodilatation (MR = 113.5 ± 6.1%; EC50 = 10.92 ± 2.81 μg/mL; n=6). This result indicates that both EDP and FDP act on voltage-operated calcium channel (Cav). Furthermore, EDP and FDP (0.03; 0.3; 10; 30 e 100 μg/mL) antagonized CaCl2-induced contractions. The extract also induced vasodilatation in the contraction evoked by L-type Ca2+ channel agonist (Bay K 8644, 200 nM) (MR = 113.3 ± 6.7%; EC50 = 19.45 ± 6.66 μg/mL, n=7). These results suggest that EDP induces hypotension and bradycardia. Both EDP and FDP induce endotheliumindependent vasodilatation that involves the inhibition of the Ca2+ influx through blockade of Cav.